PENGARUH VARIASI KADAR GETAH SAGU (Metroxylon sagus Rottb) SEBAGAI BAHAN PENGIKAT TERHADAP SIFAT FISIK DAN PELEPASAN TABLET DEXAMETHASON - sugiyono sugiyono; Irawan Sukma (Universitas Wahid Hasyim Semarang, 2015)
ABSTRACT Sago resin is the exudat from the plant sago (Metroxylon sagus Rottb.) from of gels and substances classified as anionic polysaccharides, colloidal nature with consistency and power of adhesive material resembling, it can be used as a binder tablets. This study aims to determine the effect of differences levels of sago resin variation as the ingredient binder dexamethason tablet the physical properties and release. Sago resin comes from the plant of sago then filtered (cleaned of impurities), blended into a fine powder to the next level with mucilago made FI (1%); FII (3%); FIII (5%); FIV (7%) and FV (10%). The sago resin mucilago is used a binder in the manufacture of granule with wet granulation method. The physical properties tested of the granule include flow time, repose of angle and compresibility. Tablets obtained its physical an chemical properties of the tested include uniformity of weight, hardness, friability, disintegration time, disolution and determination of concentration the active substances. The data obtained analyzed by comparing the theoretical approach with the relevant literature and statistically analyzed using corellation regretion alalyzed with a level of 95% The results obtained showed that the granules and tablets of all formulas meet the requirements of physical and chemical properties of a good tablet. The addition concentration of the sago resin as a binder causes the tablet hardness and disintegration time there is a significant difference between the formulas, while the release of the active substance and content uniformity tablets is not influenced by the increase in the concentration of sago resin. Keywords: Sap Sago, Wet Granulation, Dexamethason Tablet